A two-phase simulation of convective heat transfer characteristics of water–Fe3O4 ferrofluid in a square channel under the effect of permanent magnet. (25th January 2019) - Bahiraei, Mehdi; Hangi, Morteza; Rahbari, Alireza
Highlights: Numerical simulation of hydrothermal characteristics of water–Fe3 O4 ferrofluid. Ferrofluid in a square channel in presence of magnetic field of permanent magnets. Performing parametric study to analyzing the effect of different parameters. Creation of mixing in the flow and disturbance in the boundary layer development. Local enhancement in convective heat transfer. Abstract: In this numerical study, the hydrothermal characteristics of the water–Fe3 O4 ferrofluid are investigated using the two-phase mixture model. The ferrofluid flows in a square channel and is under the effect of magnetic field produced by permanent magnet(s). A parametric study is performed to analyze the effect of different factors such as nanoparticles concentration and diameter, Reynolds number and magnet strength. It is observed that applying such magnetic field creates mixing in the flow and disturbance in the boundary layer development, leading to local enhancement in the convective heat transfer at regions close to the magnet position. Higher enhancement in heat transfer is observed when the ferrofluid with higher concentration and particle size is used. Using stronger magnets also improves the heat transfer rate, and the amount of enhancement is limited by the magnetic saturation phenomenon. Increasing the Reynolds number at a given magnet strength decreases the effectiveness of the applied magnetic field on the flow and heat transfer. To create more efficient mixing in the flow and disturbance in the boundary layer, four magnets at different positions are used. It is observed that the average convective heat transfer coefficient in case of using four magnets is about 40.79% and 58.19% higher than those of using no magnet with ferrofluid and pure water, respectively.